Urban teens in the library research and practice - Agosto, Denise E.; Hughes-Hassell, Sandra; Agosto, Denise E.; IG Publishing (Chicago American Library Association, 2010)
"Urban Teens in the Library" is the perfect solution for the concerns and uncertainty many librarians face when supporting this group of patrons and students. From a team of experts who have researched the information habits and preferences of urban teens to build better and more effective school and public library programs, this book will show readers: the importance of moving beyond stereotypes and revamping library services; the value of street lit and social networking; and, how a library website can meet the information needs of teens. This groundbreaking book is relevant to all librarians working with urban teens and looking for ways to reach out to them.
Who are urban teens, and what does "urban" mean, anyway? / Denise E. Agosto and Sandra Hughes-Hassell -- Moving beyond the stereotypes: seeing urban teenagers as individuals / Sandra Hughes-Hassell, Lewis Hassell, and Denise E. Agosto -- Revamping library services to meet urban teens? everyday life information needs and preferences / Denise E. Agosto and Sandra Hughes-Hassell -- Developing a leisure reading program that is relevant and responsive to the lives of urban teenagers : insights from research / Sandra Hughes-Hassell -- Street lit: before you can recommend it, you have to understand it / Vanessa J. Irvin Morris, with Denise E. Agosto and Sandra Hughes-Hassell -- Urban teens, online social networking, and library services / June Abbas and Denise E. Agosto -- Urban teens and their use of public libraries / Denise E. Agosto -- Public library websites and urban teenagers? health information needs / Sandra Hughes-Hassell and Dana Hanson-Baldauf -- Spacing out with young adults: translating YA space concepts into practice / Anthony Bernier -- Youth development and evaluation: lessons from "Public Libraries as Partners in Youth Development" / Elaine Meyers -- The loft at Imaginon: a new-generation library for urban teens / Michele Gorman, Amy Wyckoff, and Rebecca L. Buck -- Before it?s reading, it?s writing: urban teens as authors in the public library / Autumn Winters and Elizabeth J. Gregg -- Following and leading teens online: using digital library services to reach urban teens / Kara Reuter ---et al.
Electronic reproduction.
Keywords: Young adults' libraries -- United States; Libraries and teenagers -- United States; Libraries and metropolitan areas -- United States; Internet in young adults' libraries -- United States; Urban youth -- Books and reading -- United States; Electronic books